Validation of the Classification of Intraoperative Complications for Gastrointestinal Surgery - Mert Mahsuni Sevinç; Erdem Kınacı; Ufuk Oğuz Idiz; Selim Doğan; Cihad Tatar (İstanbul Medical Journal, 2022)

(untitled)
Introduction:In recent, a new classification system for intraoperative adverse events (iAEs) was proposed, called “the Classification of Intraoperative Complications (CLASSIC).” Our aim was to evaluate the relationship between CLASSIC and the grade of postoperative complications (PostC) in gastrointestinal oncological surgery.Methods:Demographics, preoperative laboratory parameters, grades of iAEs, grades of PostC, and intraoperative pH and lactate levels were evaluated in patients who underwent gastric and colorectal surgery.Results:A total of 95 patients were included in this study. Mean age was 60±14, 57 male vs 38 females. There was no significant relationship between the grade of iAEs and PostC in terms of demographics and the presence of intraoperative acidosis. Preoperative albumin level was inversely proportional to the grade of iAEs. There was no relationship between the grade of iAEs and the grade of PostC (p=0.563). The actual rates of high-grade PostC in patients with low-grade iAEs and high-grade iAEs were 10% and 18%, respectively. Additionally, the length of stay was higher in patients with high-grade iAEs (p=0.018).Conclusion:CLASSIC may be a predictive of the grade of PostC in patients who undergo gastrointestinal surgery. High-grade iAEs is a valuable predictor of increased hospital stay.